Research advance in correlation between childhood asthma and gut microbiota - Ma, Yucong; Zheng, Haoqi; Tian, Hai; Cui, Jingjing; Liu, Li (Frontiers in Cellular and Infection Microbiology, 2025)
Asthma remains a highly prevalent and heterogeneous chronic respiratory disease in the pediatric population. Accumulating evidence has established a critical role of the gut–lung axis in the pathogenesis of asthma. Specifically, gut microbiota constituents such as Lactobacillus and Bifidobacterium species have been closely associated with childhood asthma. Current intervention strategies targeting the gut microbiota show considerable promise. Probiotic supplementation and short-chain fatty acids (SCFAs) have demonstrated the ability to restore microbial homeostasis and suppress type 2 inflammation. Additionally, phytogenic compounds exhibit potential in reshaping the gut microbial composition and ameliorating asthma symptoms. This review synthesizes clinical and mechanistic evidence from both human and animal studies, highlighting the translational potential of microbiota-targeted therapies. Future research should prioritize the development of personalized microbiota-based interventions to improve clinical outcomes in children with asthma.